Characterization of bimodal chronotype and its association with sleep: A population-based study. (21st April 2017) - Tempaku, Priscila Farias; Ramirez Arruda, Juliana; Mazzotti, Diego Robles; Gonçalves, Bruno S. B.; Pedrazzoli, Mário; Bittencourt, Lia; Tufik, Sergio
ABSTRACT: The circadian system coordinates internal events in a daily schedule to make sure that the body systems are synchronized to environmental time and internal cues. One important behavioral aspect of the circadian system is the chronotype. It is usually assessed through subjective questionnaires, being the Horne-Ostberg Morningness–Eveningness Questionnaire (MEQ) one of the most used. It classifies individuals into three major categories: morning, evening, and intermediate types. Recently, it has been hypothesized the existence of a fourth chronotype, the bimodal type, through an algorithm derived from the MEQ responses. Bimodals answer as morning-types in some questions, and as evening-types in others, resulting in an intermediate total score. To better characterize this phenotype, the present study aimed to detect and characterize the frequency of the bimodal chronotype in the EPISONO, a large population-based cohort, as well as to verify the association between bimodality and sleep parameters and genetic variation in the PER3 gene. Of the 1, 042 individuals who participated of the EPISONO, 857 had MEQ filled correctly. We found that 16% of our sample were bimodal types. We observed that bimodal individuals were significantly younger and had lower body mass index. The association between PER3 VNTR genotype and gender with bimodal chronotype was not significant. However, we found an association between bimodality and Epworth Sleepiness Scale (EES) and apnea-hypopnea index (AHI). We did not find a statistically significant difference between bimodals and intermediate non-bimodals for the studied variables. Lastly, it was observed that the most significant predictors for bimodal chronotype were female gender, AHI, and EES. In conclusion, the present work provides more evidence that the bimodal type might have to be considered when classifying chronotype and its association with young age and sleepiness may be due to the influence of social and environmental factors.